2021
DOI: 10.32598/jsmj.20.4.2424
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Spinal Cord KIF1B Protein In Healthy and Diabetic Neuropathic Wistar Rats With in Adaptation to Aerobic Training (KIF1B Changes in Sensory Neurons After Exercise)

Abstract: Background and Objectives Diabetic neuropathy is one of the most common complications of diabetes and no suitable drug treatment has been found for this complication. The aim of this study was to determine the effect of six weeks of aerobic exercise on KIF1B protein in the sensory part of the spinal cord in rats with diabetic neuropathy. Subjects and Methods In the present experimental study, 12 male Wistar rats were divided into 4 groups: healthy exercise, control exercise, healthy diabetes and control diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Exercise, as a non-drug pathway, exerts a beneficial effect in the treatment of DPN axonal transport defects. Endurance exercise inhibits the increase of KIF5, KIF1B, Dynein and other molecular motor protein contents in SCN of DPN rats ( 237 ), promotes axonal transport, and ameliorates nerve damage ( 238 , 239 ). Diabetic rats treated with gangliosides have been proven to prevent the progression of MNCV deficiency ( 240 – 243 ), and another study showed that gangliosides protect against impaired axonal transport of different molecular versions of acetylcholinesterase in diabetic animals ( 242 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise, as a non-drug pathway, exerts a beneficial effect in the treatment of DPN axonal transport defects. Endurance exercise inhibits the increase of KIF5, KIF1B, Dynein and other molecular motor protein contents in SCN of DPN rats ( 237 ), promotes axonal transport, and ameliorates nerve damage ( 238 , 239 ). Diabetic rats treated with gangliosides have been proven to prevent the progression of MNCV deficiency ( 240 – 243 ), and another study showed that gangliosides protect against impaired axonal transport of different molecular versions of acetylcholinesterase in diabetic animals ( 242 ).…”
Section: Discussionmentioning
confidence: 99%